Pemahaman Terhadap Hadis Maudhu’: Analisis Terhadap Kredibilitas Sumber dan Implikasinya dalam Penyelidikan Hadis - Nurhidayati . (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
When conducting research on Hadith, it is important to have a reliable reference. The reference used in Hadith research is the rule of validity of Hadith. Research on Hadith is carried out by analyzing the sanad, matan, and Hadith narrators to determine its validity, because a Hadith is categorized as authentic if it meets the provisions or rules for the validity of the sanad and matan Hadith. This research is a type of library research which is descriptive analytical in nature. This research aims to explain problems related to fake hadith or Maudhu' hadith. False hadith or Maudhu' hadith refers to lying words that are created and fabricated by someone, then attributed to the Prophet sallallaahu 'Alaihi Wa Sallam. False hadith is considered the worst type of hadith, some scholars even consider it a separate type apart from Dhaif hadith. All scholars agree that narrating or conveying the Maudhu' hadith is haram, unless it is stated that the hadith is fake. However, these false hadiths have spread widely in society, so it is important to provide education to the public so that they know the law.